1995
DOI: 10.1016/0160-4120(95)00006-2
|View full text |Cite
|
Sign up to set email alerts
|

Review of strategies for modelling the environmental fate of pesticides discharged into riverine systems

Abstract: International audiencePesticides are often produced and stored in large quantities near rivers posing a potential hazard for the aquatic environment. Accidental incidents such as storage facility fires are of major concern as significant amounts of pesticide chemicals can enter the nearby riverine System, possibly causing considerable environmental damage. This paper discusses and reviews the major physical, chemical, and microbiological fate processes of selected herbicides in riverine Systems. Glyphosate, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
10
0
4
Order By: Relevance
“…The K d and Koc values have often been used for predicting the pesticide concentration in aquatic environments. [26] The K d and Koc values of herbicides in this study are calculated and shown in Table 5. The Koc values obtained in this study were higher than those for soils reported by the previous study (Tables 1 and 4).…”
Section: Adsorption and Desorption Isothermsmentioning
confidence: 99%
“…The K d and Koc values have often been used for predicting the pesticide concentration in aquatic environments. [26] The K d and Koc values of herbicides in this study are calculated and shown in Table 5. The Koc values obtained in this study were higher than those for soils reported by the previous study (Tables 1 and 4).…”
Section: Adsorption and Desorption Isothermsmentioning
confidence: 99%
“…Interaction and movement between these different compartments (river, estuary, sea, atmosphere, groundwater and land) are studied through mathematical models and on the basis of molecular structure [61,62]. In each compartment, and also at different sites within a single compartment, different chemical reactions can take place due to different conditions (pH, pE, temperature, light, etc.).…”
Section: Chemical Reactions In the Environmentmentioning
confidence: 99%
“…Petit et al (1995) reviewed strategies for modeling the environmental fate of pesticides discharged into riverine systems. Petit et al (1995) reviewed strategies for modeling the environmental fate of pesticides discharged into riverine systems.…”
Section: Modelingmentioning
confidence: 99%